Effects of Lactococcus lactis on the Intestinal Functions in Weaning Piglets - Yu, Dongming; Xia, Yaoyao; Ge, Liangpeng; Tan, Bie; Chen, Shuai (Frontiers in Nutrition, 2021)
Post-weaning diarrhea of piglets is associated with gut microbiota dysbiosis and intestinal pathogen infection. Recent studies have shown that Lactococcus lactis (L.lactis) could help suppress pathogen infection. This study aimed to investigate the effects of L.lactis on various factors related to growth and immunity in weaning piglets. The results showed that L.lactis improved the growth performance, regulated the amino acid profile (for example, increasing serum tryptophan and ileal mucosal cystine) and the intestinal GABAergic system (including inhibiting ileal gene expression of SLC6A13, GABAAρ1, π, θ, and γ1, and promoting ileal GABAAα5 expression). L.lactis also modulated intestinal immunity by promoting jejunal interleukin 17, 18, 22, ileal toll-like receptor 2, 5, 6, and myeloid differentiation primary response protein 88 gene expression while inhibiting jejunal interferon-γ and ileal interleukin 22 expressions. L.lactis highly affected the intestinal microbiota by improving the beta diversity of gut microbiota and the relative abundance of Halomonas and Shewanella. In conclusion, L.lactis improved the growth performance and regulated amino acid profiles, intestinal immunity and microbiota in weaning piglets.